Therapeutic Efficiency of Immobilized Preparation of Antibiotic and Probiotic After Low Temperature Storage - Babinets, Olga M.; Vysekantsev, Igor P.; Martsenyuk, Valentina F. (Problems of Cryobiology and Cryomedicine, 2015)
N/A